Four-month-old infants' long-term memory for a stressful social event. - Rosario Montirosso; Ed Tronick; Francesco Morandi; Francesca Ciceri; Renato Borgatti (PLoS ONE, 2013)
Infants clearly show an early capacity for memory for inanimate emotionally neutral events. However, their memory for social stress events has received far less attention. The aim of the study was to investigate infants' memory for a stressful social event (i.e., maternal unresponsiveness during the Still-Face paradigm) after a 15-day recall interval using changes in behavioral responses and salivary post-stress cortisol reactivity as measures of memory. Thirty-seven infants were exposed to social stress two times (experimental condition); the first time when they were 4 months of age and second exposure after a 2 week interval. Infants in the control condition (N = 37) were exposed to social stress just one time, at the age corresponding to the second exposure for infants in the experimental condition (4 months plus 2 weeks). Given individual differences in infants' reactivity to social stress events, we categorized infants as increasers or decreasers based on their cortisol reactivity after their initial exposure to the stress of the maternal still-face. Infants in the experimental condition, both increasers and decreasers, showed a significant change in cortisol response after the second exposure to the maternal still-face, though change was different for each reactivity group. In contrast, age-matched infants with no prior exposure to the maternal still-face showed similar post-stress cortisol reactivity to the reactivity of the experimental infants at their first exposure. There were no behavioral differences between increasers and decreasers during the Still-Face paradigm and exposures to the social stress. Thus differences between the experimental and control groups' post-stress cortisol reactivity was associated with the experimental group having previous experience with the social stress. These findings indicate long-term memory for social stress in infants as young as 4 months of age.